Modification of Dry System Cotton Delinter to Increase Machine Capacity - Fatah, Gatot Suharto Abdul; soebandi, Soebandi; Lutfi, Musthofa; Widodo, Puji (Fakultas Teknologi Pertanian Universitas Brawijaya, 2012)
Dry system delinter machine designed by Indonesian Agency for Agriculture Research and Development, Serpong, Indonesia in cooperation with Indonesian Tobacco and Fiber Crops Research Institute, Malang, Indonesia has managed to assemble a seed processing equipment delinter dry system using nitric acid. The advantages of this tool are : the process is shorter (only 2-3 hours), no sunlight compared to wet systems (sulfuric acid) which will take approximately 2-3 days and does not pollute soil and water environments. But the tool still has a weakness, where the machine is not used anymore because delinter dimensions of the machine is too big. In addition there are the seeds of cotton delinted crust layer due to heating at the contact of nitric acid vapor to cotton seeds Â rudimentary. It is therefore necessary modifications to the engine of delinter the dry system. The results have been obtained by modification of the engine delinter dry system that is able to clean the rest of cotton with good results. It has also Â improved capacity of 120 k /h to 150 kg/hour. Nitric acid vapor has been wetting the rest can be directed to the distillation, so as not to endanger the operator. Nitric acid requirements prior to 1 L to 120 kg of seed cotton, can be saved to 0.9 L for 150 kg of seed cotton. Engine capacity can be increased of 25% and the nitric acid need to save as much as 35%.Keywords: delinter dry systems, cotton, nitric acid vapor